Explaining Teachers’ Resilience and Well-being - Dinar Rizky Listyaputri,; Corry Liana,; Sri Mastuti,; Agus Suprijono,; Septina Alrianingrum,; Sumarno,; Artono, (Technium Social Sciences Journal, 2023)
Teachers as educators have a vital role in organizing education in Indonesia. The teachers' workload can potentially cause occupational stress or stress in the workplace, as experienced by other professions. The results of research on teachers' psychological well-being in Indonesia over the past few years show that teachers are indicated to experience a ¬work-life imbalance which leads them to experience stress and a deficit in resilience. It is essential to know the resilience level of teachers for the government to provide a program that focuses on improving teachers' well-being. The findings show that 31 teachers who attended the teaching profession program (Pendidikan Profesi Guru-PPG) have good resilience levels.